Virtual Commuters? The American Transnational Academic Exchangee - Wolfgang Niehues (Current Objectives of Postgraduate American Studies)
International student exchange in times of globalization faces numerous challenges. The Internet - making the world shrink to a global village - is often named one of them. How does the Internet affect the daily lives of American exchange students in Germany. Do they become virtual commuters?